2012
DOI: 10.4102/hsag.v17i1.527
|View full text |Cite
|
Sign up to set email alerts
|

The expectations of fathers concerning care provided by midwives to the mothers during labour

Abstract: Midwives have been criticised for neglecting the expectations and needs of fathers. They either ignore the fathers or pressure them into becoming more involved than they would choose, if allowed to provide support to the mothers during labour. Whilst midwives are providing woman-centred care, it is important that they remember to involve the fathers in decision-making and to acknowledge their role, expectations and needs, because the birth of a child is one of the most important events in a person’s lifetime. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 21 publications
2
8
0
Order By: Relevance
“…One barrier to fathers' involvement in decision making during labour and birth identified in the literature was poor communication with health care professionals (HPC) (Dellman, 2004;Messner, 2010;Sengane and Nolte, 2012). In a literature review examining fathers' experiences of childbirth, Dellman ( 2004) found that fathers were angry when healthcare professionals withheld information.…”
Section: Barriers To Fathers' Involvement During Labour and Birthmentioning
confidence: 99%
See 1 more Smart Citation
“…One barrier to fathers' involvement in decision making during labour and birth identified in the literature was poor communication with health care professionals (HPC) (Dellman, 2004;Messner, 2010;Sengane and Nolte, 2012). In a literature review examining fathers' experiences of childbirth, Dellman ( 2004) found that fathers were angry when healthcare professionals withheld information.…”
Section: Barriers To Fathers' Involvement During Labour and Birthmentioning
confidence: 99%
“…In a literature review examining fathers' experiences of childbirth, Dellman ( 2004) found that fathers were angry when healthcare professionals withheld information. Similarly, a qualitative study conducted in South Africa, found that poor information-giving and lack of encouragement by midwives were barriers to fathers' involvement during labour and birth (Sengane and Nolte, 2012) although it did not specify whether this involvement included decision making.…”
Section: Barriers To Fathers' Involvement During Labour and Birthmentioning
confidence: 99%
“…This type of program is expected to develop more in the future to change both community and individual behaviors. As stated in previous study, 25 policy forces people to act as expected, therefore, it would be worth applying as an intervention.…”
Section: Discussionmentioning
confidence: 69%
“…Further, community is defined as membership with a sense of identity and belonging; the members influence and are influenced by one another. 25 Therefore, interactions among community members, particularly male partners, occur naturally and shape their belief systems, behaviors, values, and knowledge levels.…”
Section: Discussionmentioning
confidence: 99%
“…Male partners who attended childbirth reported that insufficient preparation restricted their participation during childbirth (19,22,23,57,61,74,85,86,93). Male partners who had not yet attended labour and/birth voiced their concern over the kind of support they could provide to their partners (19,22,57,74,85,86,93).…”
Section: Lack Of Information and Preparation On Childbirthmentioning
confidence: 99%